THE IMPACT OF INTEGRATING MIND MAPPING WITH GROUP INVESTIGATION IN TEACHING WRITING - Laksmi Dwi Intan; Patuan Raja; Ari Nurweni (Universitas PGRI Sumatera Barat, 2025)
This study aimed to investigate the effectiveness of integrating mind mapping with group investigation compared with mind mapping. A quantitative method with quasi experimental design was employed. The participants were two second-grade classes at one of vocational high schools in Bandar Lampung. The experimental group was taught by using mind mapping with group investigation, meanwhile, the control group was taught using mind mapping. The result of the post-test showed that the experimental group achieved a higher average of 80.2 compared to 73.6 in the control group. T-test score indicated a significance value (Sig. 2-tailed) of 0.001, which is below 0.05, shows a statistically significant difference between the two groups after the students got the treatment. Moreover, the students in the experimental group demonstrated greater improvement in terms of five aspects of writing, including content, organization, vocabulary, grammar, and mechanics. These findings suggested that integrating mind mapping with group investigation is more effective in improving students’ writing achievement that using mind mapping.